2011
DOI: 10.4103/0971-9784.83986
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prophylactic amiodarone in patients with rheumatic valve disease undergoing valve replacement surgery

Abstract: The study was carried out to evaluate the effect of prophylactic single-dose intravenous amiodarone in patients undergoing valve replacement surgery. Maintenance of sinus rhythm is better than maintenance of fixed ventricular rate in atrial fibrillation (AF) especially in the presence of irritable left or right atrium because of enlargement. Fifty-six patients with valvular heart disease with or without AF were randomly divided into two groups. Group I or the amiodarone group (n=28) received amiodarone (3 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Compared with other antiarrhythmic drugs, amiodarone has higher conversion rate and better sinus rhythm maintenance 19. In this study, the conversion rate of atrial fibrillation and maintenance rate of sinus rhythm of the observation group were 76.2% and 47.6% respectively, which were significantly higher than those of the control group, and the results were similar to the previous research results 20,21. In addition, rate of administration ways of amiodarone can produce different effects.…”
Section: Discussionsupporting
confidence: 86%
“…Compared with other antiarrhythmic drugs, amiodarone has higher conversion rate and better sinus rhythm maintenance 19. In this study, the conversion rate of atrial fibrillation and maintenance rate of sinus rhythm of the observation group were 76.2% and 47.6% respectively, which were significantly higher than those of the control group, and the results were similar to the previous research results 20,21. In addition, rate of administration ways of amiodarone can produce different effects.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies in patients undergoing VR have administered IV amiodarone before CPB and reported reduction in incidence of AF but maintenance of long term SR was not assessed . 17 , 18 …”
Section: Discussionmentioning
confidence: 99%
“…In patients undergoing mitral valve replacement, intravenous (IV) amiodarone given before institution of cardiopulmonary bypass significantly reduced the incidence of AF after release of aortic cross clamp as well as at 24 h. 25 , 26 However these studies only used a single dose infusion and did not assess maintenance of SR over long term.…”
Section: Discussionmentioning
confidence: 99%